Presumed Cause(s) of Tuberculosis in Rural Nepal - Engelbrektsson, Ulla-Britt; Subedi, Madhusudan (Himalayan Journal of Sociology and Anthropology, 2017)
In focus is the emic perspective on cause/s of tuberculosis. The ethnographic data is from two major studies in one and the same community in the Hill district of Pyuthan, in the Mid-Western Development Region. The findings show a pooling of old and new influences with a dazzling plurality of thoughts and ideas within a framework of great uncertainty. Moreover, changes in perceptions over the last decade and an half are quite marginal. For health workers to function efficiently the perceived causes of patients and their communities need to be understood and taken into account.Himalayan Journal of Sociology & Anthropology - Vol. VII (2016), Page: 175-197